2017
DOI: 10.3390/molecules22071083
|View full text |Cite
|
Sign up to set email alerts
|

The C5 Variant of the Butyrylcholinesterase Tetramer Includes a Noncovalently Bound 60 kDa Lamellipodin Fragment

Abstract: Humans with the C5 genetic variant of butyrylcholinesterase (BChE) have 30–200% higher plasma BChE activity, low body weight, and shorter duration of action of the muscle relaxant succinylcholine. The C5 variant has an extra, slow-moving band of BChE activity on native polyacrylamide gel electrophoresis. This band is about 60 kDa larger than wild-type BChE. Umbilical cord BChE in 100% of newborn babies has a C5-like band. Our goal was to identify the unknown, 60 kDa protein in C5. Both wild-type and C5 BChE ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Physiologically BChE is mainly a tetramer through the interaction of the C-terminal helices of each monomer that is associated in a coiled coil motif around an antiparallel proline rich peptide originating from lamellipodin [ 26 , 27 , 28 ]. Some recombinant BChE productions and X-ray structures have reported the isolation of dimers of BChE and the tetrameric form can be view as a dimer of dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically BChE is mainly a tetramer through the interaction of the C-terminal helices of each monomer that is associated in a coiled coil motif around an antiparallel proline rich peptide originating from lamellipodin [ 26 , 27 , 28 ]. Some recombinant BChE productions and X-ray structures have reported the isolation of dimers of BChE and the tetrameric form can be view as a dimer of dimers.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, AChE and butyrylcholinesterase (BChE) are enzymes that hydrolyze ACh and have similar molecular forms ( Massoulié, 2002 ), both containing a catalytic domain and a similar C-terminal tetramerization domain that requires a proline-rich sequence to organize the tetramer ( Figure 1A ). Several peptides containing polyproline sequences were found in AChE and butyrylcholinesterase (BChE) tetramers ( Li et al, 2008 ; Biberoglu et al, 2012 , 2013 ; Schopfer et al, 2017 ), confirmed in the three-dimensional (3D) structure of BChE tetramer purified from the serum ( Leung et al, 2018 ; Boyko et al, 2019 ); and two proteins ColQ and proline-rich membrane anchor (PRiMA) contain a proline-rich sequence that organizes AChE and/or BChE into tetramers. PRiMA is a small transmembrane protein that anchors AChE tetramer on the plasma membrane ( Perrier et al, 2002 ; Dobbertin et al, 2009 ) and ColQ is specific collagen ( Figures 1A , 2 ) that anchors AChE tetramers in the basal lamina ( Feng et al, 1999 ).…”
Section: Organization Of the Nmj: Cholinesterasesmentioning
confidence: 90%
“…The BChE tetramer incorporates not only short polyproline-rich peptides, but also long protein fragments that contain a polyproline-rich region. An example is the C5 variant of human BChE whose tetrameric structure includes a 60 kDa lamellipodin fragment [24]. The ability of BChE monomers to assemble into stable, long-lived tetramers by binding the polyproline-rich region of a protein, suggests that BChE could serve as a delivery vehicle for any protein that has been engineered to include a polyproline-rich peptide tag.…”
Section: Bche and Ache Scavenge Polyproline Peptides Released From Proteins In The Cytoplasm Nucleus Endoplasmic Reticulum Extracellular mentioning
confidence: 99%